2012
DOI: 10.1097/prs.0b013e31822b6771
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Basis of the Facial Artery Perforator Flap

Abstract: Facial artery perforators seem to be predominantly between 1 and 2 cm lateral to the level of the oral commissure. Seven main types of perforasomes have been identified and appear to be the basis for local flap design. This study improves our understanding of facial vascularization and will allow the face to give up the era of random flaps to take advantage of more accurate reconstructions from the rest of the body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 0 publications
2
63
0
Order By: Relevance
“…One such example is the modiolus perforator flap described by Gunnarsson and Thomsen [6] wherein they describe the use of a musculocutaneous perforator in a window of soft tissue bounded superiorly by the zygomaticus major, inferiorly by the risorius, medially by the oral commissure and laterally, by the facial artery. This consistent perforating vessel has been described by other studies [7] and is the source perforator used for the perforator-plus labio-mandibular flap. However, one of the issues with the use of propeller or islanded flaps is the later onset of lymphoedema; an unaesthetic feature.…”
Section: Discussionsupporting
confidence: 83%
“…One such example is the modiolus perforator flap described by Gunnarsson and Thomsen [6] wherein they describe the use of a musculocutaneous perforator in a window of soft tissue bounded superiorly by the zygomaticus major, inferiorly by the risorius, medially by the oral commissure and laterally, by the facial artery. This consistent perforating vessel has been described by other studies [7] and is the source perforator used for the perforator-plus labio-mandibular flap. However, one of the issues with the use of propeller or islanded flaps is the later onset of lymphoedema; an unaesthetic feature.…”
Section: Discussionsupporting
confidence: 83%
“…The length of the flap should be determined so that it can cover the most distant edge of the defect with appropriate transposition or rotation movement. As described by Qassemyar et al, 6 the facial artery perforators are located predominantly between 1 and 2 cm lateral to the level of the oral commissure, and therefore this specific area should be dissected carefully to preserve the appropriate perforator. This specific knowledge should be taken into consideration in flap planning so that this perforator-rich area has to be at the base of the flap.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Pinar et al demonstrated that the external diameter of the facial artery was 2.6 mm (ranging from 1.7 to 3.6 mm) as it crossed the mandible. 16 The diameter of the artery measured in this study was 3.5 mm (Fig. 6).…”
Section: Discussionmentioning
confidence: 53%
“…12 Qassemyar et al reported that the facial artery perforators seem to be mainly located 15 mm lateral to the level of the oral commissure. 16 Squaquara et al reported that the facial artery passes upwards and forward to a point 13.8 mm (ranging from 10 to 16 mm) lateral to the commissure of the mouth. 8 Pinar et al demonstrated that the facial artery is located 15.5 mm (ranging from 9.0 to 20.2 mm) lateral to the angle of the mouth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation